HUBUNGANINFORMASI TENTANG SMK DENGAN MINAT SISWA SMP MEMILIH PROGRAM KEAHLIAN TATA BOGA DI KABUPATEN PESISIR SELATAN - Jefriyanti, Ranti; Elida, Elida; Faridah, Anni (Journal of Home Economics and Tourism, 2017)
The purpose of this study to analyze the relationships of information about vocational interests junior high school students choose skill program Culinary. This research is a quantitative correlation approach. This study population junior class IX students at the Kabupaten Pesisir Selatan academic year 2016/2017, amounting to 7,700 students with a sample of 192 students. The sampling technique by means of cluster sampling.Collecting data using a questionnaire with Likert scale and Gutman scale.The data is processed using SPSS 16. The results of this study concluded that there is a positive relationship and significant information about vocational interests junior high school students choose skill program Culinary to the count r ie: 0237 with the interpretation of the relationship is lowKey Word: information, vocational school, interest junior high school student, culinary